Agricultural transformation in Asia: An overview of recent experiences - Vos, Rob; Mamun, Abdullah; Traoré, Fousseini; Laborde Debucquet, David (Food and Agricultural Organization of the United Nations, 2021)
Structural change is a cornerstone of long-term economic development, according to economic theory and as borne out by international experience. Urbanization and industrial growth are key features of structural change. Urbanization and industrialization helped fuel the remarkable acceleration of economic growth in East Asia and parts of Southeast Asia over the past half-century. However, strong agricultural productivity growth and agrarian change were also essential ingredients of these economic ‘miracles,’ particularly during the initial stages of rapid economic acceleration, or “take-off”. The Green Revolution, reforms of agricultural and rural institutions, and public investment in rural infrastructure have been critical factors in the economic take-off of early and late successful transformers. In subsequent stages, the industrial sector, and later the service sector became the dominant drivers of overall growth. But, economic acceleration also pushed agriculture and rural economies to deeper transformative change. The expansion of cities, rising incomes and other factors led to major changes in diets that require a more industrial organization of food systems. These processes have also been taking place in South Asia and less developed parts of Southeast Asia, although they began later and are moving at a slower pace. In India and other South Asian countries, structural impediments to development including land scarcity, water stress, and weak institutions, initially constrained agricultural growth and broader economic development. As some of these impediments were lifted faster growth was unleashed. Some of the lessons from East Asia may not apply to India and South Asia. However, certain patterns will likely remain the same. In all countries, agricultural employment will decline in importance, while that of non-farm segments of the agrifood system will rise along with urbanization, income growth and dietary change. Farm efficiency and rural employment opportunities are already increasingly influenced by what happens beyond the farmgate and by the relative strength of rural–urban linkages. However, countries in the early to intermediate stages of agricultural transformation face additional challenges. Land scarcity combined with continued population pressures have led to further fragmentation of landholdings and increasing stress on already degraded land and water resources. Countries that follow past development pathways will eventually run into environmental constraints. Likewise, while structural change has dramatically reduced poverty and undernourishment in Asia, dietary and food-system changes have created new malnutrition challenges: overweight and obesity are on the rise. Policies have been critical in determining the speed of agricultural transformations in Asia. Moving forward, the focus on promoting agricultural productivity growth will have to change. Policymakers must strike a balance. They must improve farm efficiency and food value-chain development. Yet, they must also reduce food insecurity and all forms of malnutrition, while preserving environmental sustainability.